Banks' Holdings of Government Securities and Credit to the Private Sector in Emerging Market and Developing Economies - Bouis, Romain (IMF Working Papers; Working Paper, 2019)
This paper studies the relationship between banks' holdings of domestic sovereign securities and credit growth to the private sector in emerging market and developing economies. Higher banks' holdings of government debt are associated with a lower credit growth to the private sector and with a higher return on assets of the banking sector. Analysis suggests that the negative relationship between banks' claims on the government and private sector credit growth mainly reflects a portfolio rebalancing of banks towards safer, more liquid public assets in stress times and provides only limited evidence of a crowding-out effect due to financial repression.